Sistem Pendukung Keputusan Penulis Terbaik Menggunakan Metode Rank Order Centroid (ROC) dan Evaluation based on Distance from Average Solution (EDAS) - Putri Mandarani; Haula Luthfia Ramadhan; Eva Yulianti; Anna Syahrani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
CV Jejak Publisher is a publishing company who has actively held writing competitions. However, there is a problem that occurs in the assessment process that has been running. The problem is several participants get the same value of the final score which makes it difficult for the jury to determine the order of winners. Therefore, to get a fairer and clearer result, need a calculation method that can support the jury's decision for determining the winners. This study aims to design a decision support system by applying the ROC and EDAS methods. ROC is used to assign a weighted value to each of the criteria set by CV Jejak Publisher, while EDAS is used to assess and rank the data of the participants. This system has output is the rank and final score of the participants from the highest to the lowest score. As a result, the ROC and EDAS methods were successfully applied to the system, as evidenced by 110 input data and all of them were successfully ranked by the system. The highest average score is 88.4 with the highest score based on 5 scoring criteria, namely 422. Thus, this system can be used to assist the jury in making a decision on the winner.